2016
DOI: 10.17795/jjhs-37097
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Respiratory Symptoms and Spirometry Parameters of Welders in a Steel Industry

Abstract: Background: Fumes released form welding activities are capable of initiating several acute and chronic respiratory effects. Objectives: The aim of the present study was to evaluate respiratory symptoms and spirometry parameters in welders of a steel industry. Methods: This cross-sectional study was conducted in a steel industry and involved 60 welders and 40 non-welders. A questionnaire was used to record participants' details, and to determine pulmonary function values the spirometric test was used. Pearson c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…The results were in line with the results of several studies done in the past. A study done in Ahvaz, Iran reported that respiratory symptoms are more prevalent among welders than nonwelders (31). Another study was conducted on the respiratory health of a population of welders in Saudi Aramco.…”
Section: Discussionmentioning
confidence: 99%
“…The results were in line with the results of several studies done in the past. A study done in Ahvaz, Iran reported that respiratory symptoms are more prevalent among welders than nonwelders (31). Another study was conducted on the respiratory health of a population of welders in Saudi Aramco.…”
Section: Discussionmentioning
confidence: 99%
“…Research in a steel industry company in Ahvaz, Iran, discovered that welding workers experienced a significant decrease in lung function for all parameters (FVC, FEV 1 , FEF 25-75% , and FEV 1 /FVC) (56). In addition, research in Monza showed that based on the spirometry lung function tests, abnormal pulmonary function was correlated inversely with years of exposure to welding fumes (FEV 1 : R 2 = 0.303; p = 0.012; FVC: R2 = 0.27; p < 0.02).…”
Section: Meta-analysis Of Exposure To Welding Fumes In Association Wi...mentioning
confidence: 99%
“…Penelitian menunjukkan gejala pernapasan akut pada pekerja pengelasan yaitu perubahan fungsi paru. 14 Idiopathic Pulmonary Fibrosis (IPF) adalah pneumonia fibrosis interstitial kronis dan progresif yang tidak diketahui. penyebabnya yang terkait dengan pola histopatologis dan/atau radiologis dari pneumonia interstitial.…”
Section: Hasil Dan Diskusiunclassified
“…Meskipun pada penelitian tidak menunjukkan hubungan kebiasaan merokok dan fungsi paru antara pekerja dan bukan pekerja. 14 Faktor perlindungan diperkirakan rendah pada pekerja pengelasan karena pada saat pengelasan, pekerja berulang kali membuka helm pelindung untuk memeriksa lapisan pengelasan. 30 Konsentrasi materi partikulat yang tinggi di udara adalah faktor utama bahaya kesehatan yang terkait dengan polusi udara dan partikel yang lebih halus (diameter 2,5 mikrogram atau lebih kecil) semakin besar bahayanya untuk kesehatan.…”
Section: Hasil Dan Diskusiunclassified